Organisational psychology : an essential guide (New York, NY : Routledge, 2024)
"Organisational Psychology offers an accessible, engaging and practical introduction to this fascinating discipline. It explores the latest thinking, reveals surprising truths about the way we work, and explains how to craft a successful and fulfilling career in the field"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Psychology, Industrial; Organizational behavior